RE-OS ISOTOPE MEASUREMENTS OF SINGLE SULFIDE INCLUSIONS IN A SIBERIAN DIAMOND AND ITS NITROGEN AGGREGATION SYSTEMATICS - Pearson D.G.; Shirey S.B.; Bulanova G.P.; Carlson R.W.; Milledge H.J. (My University, 1999)
We have measured the Re-Os isotopic compositions of individual syngenetic sulfide inclusions from three different growth zones within a central cross section plate cut from a single Siberian diamond. Individual sulfides in their diamond host were isolated by laser cutting. The sulfides, and hence the different growth zones of the diamond have been suggested to differ in age by up to 2 Ga on the basis of their Pb isotope compositions. Re-Os model ages of the four inclusions range from 3.1 ± 0.3 to 3.5 ± 0.3 Ga and suggest a Middle Archaean age for the diamond. A sulfide inclusion in the rim of the diamond is very different in elemental composition from those of the core and intermediate zones. It is enriched in Os, Re, Pb, and Zn and has more radiogenic Os and Pb isotopes. The inclusion is connected to the surface of the diamond by a healed crack, revealed by cathodoluminescence. The compositional distinction may be caused either by postformational interaction between an ancient sulfide and a fluid, possibly at the time of kimberlite eruption, or later stage growth of new diamond plus sulfide. Such chemical complexities, and the presence of healed fractures within the host diamond, emphasize the desirability of analyzing individual inclusions from well-characterized diamonds if isotope data for inclusions are to be better understood.
Keywords: Archaean; Precambrian::Archean; Докембрий::Архей